The Role of Grit on Students' Academic Success in Experiential Learning Context - Li, Jiaze; Li, Yang (Frontiers in Psychology, 2021)
Students’ success as a cognitive issue in learning is prejudiced by proper learning approaches which improve their comprehension and achievement. In an attempt to scrutinize supplementary or alternate variables that envisage students’ success, the researcher inspected a non-cognitive factor, namely grit, theorized as passion and perseverance due to its long-term quality, on the one hand, and its popularity among scholars in preceding decades on the other hand. Moreover, experiential learning (EL) is a momentous instructional approach used in the educational process to accelerate ‘do it and learn’. The proposed review aims to gauge the EL approach as well as grit to regulate learners’ educational success. Consequently, some pedagogical implications are presented for teachers, students, and syllabus designers.